2010
DOI: 10.3233/jad-2010-1335
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Peptide NAP Does Not Directly Affect Polymerization or Dynamics of Reconstituted Neural Microtubules

Abstract: NAP (Asn-Ala-Pro-Val-Ser-Ile-Pro-Gln) is a neuroprotective peptide that shows cognitive protection in patients with amnestic mild cognitive impairment, a precursor to Alzheimer's disease. NAP exhibits potent neuroprotective properties in several in vivo and cellular models of neural injury. While it has been found in many studies to affect microtubule assembly and/or stability in neuronal and glial cells at fM concentrations, it has remained unclear whether it acts directly or indirectly on tubulin or microtub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…NAP is a multi-functional peptide that protects neural cells. In previous studies, it was indicated that the NAP could prevent the ethanolinduced developmental toxicity, embryotoxicity, and has potential importance of ethanol effects on the pathophysiology of fetal alcohol syndrome (FAS) [47,48]. In AD research, the Apo E has been implicated as a risk factor.…”
Section: Ad-related Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…NAP is a multi-functional peptide that protects neural cells. In previous studies, it was indicated that the NAP could prevent the ethanolinduced developmental toxicity, embryotoxicity, and has potential importance of ethanol effects on the pathophysiology of fetal alcohol syndrome (FAS) [47,48]. In AD research, the Apo E has been implicated as a risk factor.…”
Section: Ad-related Proteinsmentioning
confidence: 98%
“…In AD research, the Apo E has been implicated as a risk factor. The NAP is the neuroprotective peptide of Apo E deficiency and is able to break the amyloid plaque formation or degrade the β-amyloid toxicity [48,49]. Neurofibrillary tangles composed of aggregation, which are formed by hyperphosphorylated tau protein, are one of the major pathological hallmarks of AD.…”
Section: Ad-related Proteinsmentioning
confidence: 99%
“…Intranasal administration of davunetide is undergoing phase II clinical trials for the treatment of tauopathies, including PSP, frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17), CBD and progressive non-fluent aphasia (http://www.clinicaltrials.gov/ct2/show/NCT01056965). The main pharmacological action of davunetide is thought to be stabilisation of MTs in neurons,43 although the drug has other pleiotrophic effects and does not directly affect the polymerisation or dynamics of reconstituted neural MTs 44…”
Section: Therapeutic Strategies For Tau Mediated Neurodegenerationmentioning
confidence: 99%
“…In spinal cord injury and optic nerve crush models, local administration of paclitaxel improves axonal regeneration and motor function (Hellal et al, 2011;Sengottuvel et al, 2011). In addition, NAP, a peptide with possible indirect MT-stabilizing activity (Yenjerla et al, 2010), has pathological and behavioral benefits in several tauopathy models (Gozes et al, 2009). NAP is in Phase II clinical trials for tauopathy.…”
Section: Introductionmentioning
confidence: 99%